2021
DOI: 10.1080/21663831.2020.1868593
|View full text |Cite
|
Sign up to set email alerts
|

Large bias-induced piezoelectric response in the ferroelectric polymer P(VDF-TrFE) for MEMS resonators

Abstract: Piezoelectricity in ferroelectrics arises from electrostriction biased by their spontaneous polarisation, which can be enhanced through a bias-induced polarisation. Doing so, the piezoelectric response can be tuned and significantly enhanced. In this study, the ferroelectric polymer P(VDF-TrFE) was used to electro-mechanically excite a silicon microcantilever. Using this device, we demonstrate that a bias-induced polarisation improves the piezoelectric response of P(VDF-TrFE). To distinguish between the linear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
(65 reference statements)
2
4
0
Order By: Relevance
“…This phenomenon resulted from the formation of grain boundaries in the film, which scattered light, causing the film to appear foggy. the results have shown that an annealing temperature that is closer to the melting temperature causes the annealing treatment to be more effective at increasing the crystallinity of the film, this phenomenon is similar to other literature studies. The β-phase content is the key influencing factor in a film’s piezoelectric response. Therefore, this experiment used FT-IR spectroscopy for quantitative analysis.…”
Section: Resultssupporting
confidence: 85%
“…This phenomenon resulted from the formation of grain boundaries in the film, which scattered light, causing the film to appear foggy. the results have shown that an annealing temperature that is closer to the melting temperature causes the annealing treatment to be more effective at increasing the crystallinity of the film, this phenomenon is similar to other literature studies. The β-phase content is the key influencing factor in a film’s piezoelectric response. Therefore, this experiment used FT-IR spectroscopy for quantitative analysis.…”
Section: Resultssupporting
confidence: 85%
“…and Chen et al., this piezoelectric response can be significantly enhanced by an applied electric field, which was also applicable to our PVMFET. [ 58,59 ] To confirm this, we measured the electrical potential applied between source/drain electrodes and floating gate, namely V F , simultaneously under various applications of gate voltage and bending angle. Basically, in PVMFET, the V F generates an effective vertical electric field contributing to form FET channel.…”
Section: Resultsmentioning
confidence: 97%
“…The outputs for the TPHNG are slightly higher than those for the neat TENG (V oc ~46 V, I sc ~1.4 µA), which indicates that there exists a coupling effect between the TENG and PENG in the hybrid system (Figure 3a,b). The phenomenon can be explained by the poled P(VDF-TrFE-CFE) in PENG producing intrinsic charges on both electrodes in PENG [37], which induces an initial charge accumulation on the copper trips in the TENG, resulting an enhancing effect similar to a charge injection [38]. On the other hand, the waveform patterns of sliding with the hybrid device are similar to those of the neat sliding mode TENG.…”
Section: Structure Working Principle and Electric Outputs Of Hybrid N...mentioning
confidence: 92%